2022
DOI: 10.1002/ceat.202100496
|View full text |Cite
|
Sign up to set email alerts
|

Reuse Potential of Refinery Wastewater Treated Using a Two‐Stage Submerged Membrane Bioreactor

Abstract: Refinery wastewater treatment was performed using a novel submerged tubular ceramic membrane bioreactor (STMBR) with the oleaginous hydrocarbonoclastic bacterium Rhodococcus opacus. A membrane‐based flux study with the STMBR was carried out to assess the performance of the tubular ceramic membrane. Continuous experiments with the STMBR achieved a maximum chemical oxygen demand (COD) removal of 84 %, with an average flux of 0.4 × 10−3 m3m−2s−1. To further enhance the COD removal efficiency, two STMBR were opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…These hydrophilic nanoparticles were also found to increase the intensity of membrane penetration, which causes the membranes to keep onto more water. Additionally, the percentage of water content reduced slightly with the addition of 2 wt % compared to 1.5 wt % might be due to the agglomeration of nanoparticles [38][39][40].…”
Section: Water Content and Porosity Analysis Of Prepared Membranesmentioning
confidence: 98%
“…These hydrophilic nanoparticles were also found to increase the intensity of membrane penetration, which causes the membranes to keep onto more water. Additionally, the percentage of water content reduced slightly with the addition of 2 wt % compared to 1.5 wt % might be due to the agglomeration of nanoparticles [38][39][40].…”
Section: Water Content and Porosity Analysis Of Prepared Membranesmentioning
confidence: 98%
“…Many studies have been reported on bioreactor working conditions for achieving high treatment efficiency and low sludge production in ASP. However, the recent focus is on the use of a membrane in the bioreactor, which serves to retain the sludge or microorganisms as well as improve the removal efficiency (Paul et al., 2022).…”
Section: Treatment Of Petroleum Refinery Wastewater (Prww)mentioning
confidence: 99%